2011
DOI: 10.1111/j.1748-7692.2011.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of thyroid morphology during different reproductive events in female Indo‐Pacific bottlenose dolphins, Tursiops aduncus

Abstract: Thyroid morphology and function are likely affected by the cyclic hormonal environment during different reproductive events in females. The present study was undertaken to evaluate the variation of thyroid morphology at different reproductive events (anestrus, estrus, lactation, and pregnancy) in a captive group of Indo‐Pacific bottlenose dolphins (Tursiops aduncus) measured using sonography. Sonographic examinations of the thyroid gland and ovaries in nine sexually mature female subjects were performed weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…65 When a dolphin reaches sexual maturity, thyroid physiology becomes further complicated by cyclic influences of sex hormones in females; in males, these influences are not as pronounced. 66 The present study revealed that sexually immature males had significantly (P < 0.001) greater thyroid volume than did sexually immature females, whereas sexually mature females had significantly (P < 0.001) greater thyroid volumes than did sexually mature males. Sexual bimaturism is a typical feature of marine mammals.…”
Section: Discussionsupporting
confidence: 45%
“…65 When a dolphin reaches sexual maturity, thyroid physiology becomes further complicated by cyclic influences of sex hormones in females; in males, these influences are not as pronounced. 66 The present study revealed that sexually immature males had significantly (P < 0.001) greater thyroid volume than did sexually immature females, whereas sexually mature females had significantly (P < 0.001) greater thyroid volumes than did sexually mature males. Sexual bimaturism is a typical feature of marine mammals.…”
Section: Discussionsupporting
confidence: 45%
“…Similar to lactating wild bottlenose dolphins (Fair et al, 2011), we found a significant increase in t T 3 , and a non-significant decrease in t T 4 (9%) compared with adult non-pregnant non-lactating females, and a corresponding significant increase in t T 3 :t T 4 during lactation in the boto. These results are also compatible with an observed increase in thyroid size in wild lactating bottlenose dolphins (Cowan and Tajima, 2006) and an observed increase in thyroid volume during lactation in captive Indo-Pacific bottlenose dolphins ( Tursiops aduncus , Kot et al, 2012). Whether the observed thyroid hypertrophy was a residual effect from the known goitrogenic effects of pregnancy, as has been observed in humans (Glinoer, 2004), or a true response to increase demand during lactation for thyroid hormone is unknown.…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, this phenomenon was not observed in captive or wild bottlenose dolphins (Fair et al, 2011; West et al, 2014), whereby their diet which consist of marine fish typically have an overabundance of iodine (Ridgway and Patton, 1971), whereas the fresh water fish food source on which the boto rely for are a magnitude lower in iodine content (Eckhoff and Maage, 1997; Fordyce, 2003). It has been noted that wild pregnant and captive bottlenose dolphins had increased thyroid gland mass compared with non-pregnant females (Cowan and Tajima, 2006; Kot et al, 2012), and the goiterogenic effects of moderate iodine restriction during pregnancy in humans are well documented (Glinoer, 2004). In addition to possible iodine deficiency, the change in T 3 : T 4 could simply indicate the inability of the thyroid to keep up with high metabolic demands of late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in the ultrasonographic appearance and volume of the thyroid gland were noted in this species [23]. Different cetacean species have variations in thyroid gland morphology and function, which are associated with demographic variables, physiological cycles and health status [10],[11],[23][25]. Determining volume is important in assessing the development and involution of the thyroid gland, but volume estimation is also important in stereological studies.…”
Section: Introductionmentioning
confidence: 90%